How to market design consultancy services finding, winning and keeping clients - Preddy, Shan (Design Council/Gower, 1997)
Targetted at design consultancies, this book provides an introductory guide to starting off in business as well as explaining new techniques for design professionals. Marketing strategies and implementation plans are dealt with and case studies are examined.